Integrin-Mediated Tumorigenesis and Its Therapeutic Applications - Li, Qingling; Lan, Ting; Xie, Jian; Lu, Youguang; Zheng, Dali; Su, Bohua (Frontiers in Oncology, 2022)
Abstract: Integrins, are a family of adhesion molecule generally exist on the cell surface, and essential to regulate cell growth and its functions. As a bi-directional signaling molecule, it mediates cell-cell and cell-extracellular matrix interaction. The recognitions of its key roles in many human pathologies, including autoimmunity, thrombosis and neoplasia, have revealed great potential as a therapeutic target. This paper focuses on the structure, activation, the role of integrins in tumorigenesis and progression, and advances of integrin-dependent tumor therapeutics in recent years. It is expected that by understanding function and signaling transmission will fully exploit potentialities of integrin emerging as a novel target for tumors.